2022
DOI: 10.1038/s42003-022-04269-w
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and hydroxymethylation characterize the identity of D1 and D2 striatal projection neurons

Abstract: Neuronal DNA modifications differ from those in other cells, including methylation outside CpG context and abundant 5-hydroxymethylation whose relevance for neuronal identities are unclear. Striatal projection neurons expressing D1 or D2 dopamine receptors allow addressing this question, as they share many characteristics but differ in their gene expression profiles, connections, and functional roles. We compare translating mRNAs and DNA modifications in these two populations. DNA methylation differences occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 94 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…hmCG then demonstrated a positive association with expression in the gene body. While this relationship has been described in neurons [3,4,102], the relationship of hmCG to expression has not been characterized in astrocytes and microglia and provides strong evidence that hmCG is a genome regulator in glial cell types of the CNS as well as neurons. While no discernable associations between astrocytic and microglial mCH were clear, greater sequencing depth could help resolve this.…”
Section: Discussionmentioning
confidence: 99%
“…hmCG then demonstrated a positive association with expression in the gene body. While this relationship has been described in neurons [3,4,102], the relationship of hmCG to expression has not been characterized in astrocytes and microglia and provides strong evidence that hmCG is a genome regulator in glial cell types of the CNS as well as neurons. While no discernable associations between astrocytic and microglial mCH were clear, greater sequencing depth could help resolve this.…”
Section: Discussionmentioning
confidence: 99%
“…hmCG then demonstrated a positive association with expression in the gene body. While this relationship has been described in neurons [ 3 , 4 , 112 ], the relationship of hmCG to expression has not been characterized in astrocytes and microglia and provides strong evidence that hmCG is a genome regulator in glial cell types of the CNS as well as neurons. While no discernable associations between astrocytic and microglial mCH were clear, greater sequencing depth could help resolve this.…”
Section: Discussionmentioning
confidence: 99%
“…These three studies also consistently reported differences in pathways related to nervous system development and synapse function, even in non-neural tissues. This link should be further explored, as small, sparse, and local differences in hydroxymethylation have been associated with gene expression ( Marion-Poll et al, 2022 ), potentially representing a “fine tuning” mechanism of gene regulation that is linked with transcription factor recruitment ( Lercher et al, 2014 ). Because the brain is the primary target organ of Pb toxicity, collective results may be revealing differences in hydroxymethylation patterns that underlie the link between developmental Pb exposure and later life neurotoxic effects.…”
Section: Discussionmentioning
confidence: 99%